Distribution and habitat preference of Carabidae and Staphylinidae (Coleoptera) in an orange orchard and a forest fragment - Cividanes, Francisco Jorge [UNESP]; Araujo, Edileusa S. [UNESP]; Ide, Sergio; Galli, Julio Cesar [UNESP] (Florida Entomological Soc, 2010)
A survey of Carabidae and Staphylinidae (Coleoptera) was conducted in a forest fragment and an orange orchard located in the Gaviao Peixoto municipality, São Paulo State, Brazil to identify dominant predator species that may be important in the biocontrol of orange pests. Beetles were captured by pitfall traps arranged along 2 parallel transects 200 m long, placed across the orchard/forest boundary, extending 100 m into each habitat. The Shannon-Wiener diversity and Bray-Curtis similarity indices were calculated for both habitats, and habitat preference of abundant species were investigated by analysis of variance. Carabids comprised 91% and 86% of the beetles observed in the fragment and orchard, respectively. Abaris basistriata Chaudoir, Athrostictus sp.1, Tetracha brasiliensis (Kirby), Pseudabarys sp.1, Selenophorus seriatoporus Putzeys, Selenophorus sp.4, and the staphylinid Xenopygus sp.2 were the dominant species. There was no significant increase or decrease in carabid and staphylinid species richness from the edge to the interior of the fragment and orchard. Abaris basistriata prefered the forest fragment and the orange orchard, while Athrostictus sp.1, Pseudobarys sp., Selenophorus sp.4, and S. seriatoporus were orchard associated. The presence of ground vegetation on the orchard soil can have favored the establishment of ground-dwelling beetles that may be acting to control important orange pests. Dominant species determined in this study should be considered in future researches aiming to enhance the biocontrol in orange orchards.
Keywords: Biological control; Citrus sinensis; diversity; similarity indices